Analysis of tubular joints in marine structures: A comprehensive review - Zavvar, Esmaeil; Rosa-Santos, Paulo; Ghafoori, Elyas; Taveira-Pinto, Francisco (Marine structures, 2025)
The use of tubular joints (TJs) is evident, although they are commonly utilized in different areas, such as buildings, bridges, offshore structures, and renewable energy structures. Many studies have been conducted on TJs to better understand their behavior from different perspectives, namely using the Stress Concentration Factor (SCF), Hot-Spot Stress (HSS), Fatigue, Stress Intensity Factor (SIF), Degree of Bending (DoB), Local Joint Flexibility (LJF), among others. This paper reviews the experimental and numerical studies published in Web of Science from 1965 until 2024. Several studies have been considered in order to enhance comprehension and summarize existing design guidelines, recommendations, and codes. It was found that single-planar joints had more interest among scholars, especially T, Y, and K-joints, therefore, multi-planar joints need extensive investigations. In addition, the most common studied loadings are axial, in-plane bending, and out-of-plane bending. Hence, to have more accurate results, it is suggested to direct future research to modeling and analysis of the whole platform under environmental conditions. •This study reviewed run- and reinforced tubular joints.•This study reviewed the sSCF, HSS, fatigue, SIF, DoB, and LJF in tubular joints.•A comprehensive review of experimental and numerical studies.•Several issues have been identified and require extensive investigation.